Experimental studies of dual electric induction spherical electric field intensity sensor in inhomogeneous field of point source - S. V. Biryukov; L. V. Tyukina; A. V. Tyukin (Омский научный вестник)
In the work, dual electroinductive spherical sensors, which are a constructive combination of two double sensors into one, are subjected to experimental studies in a non-uniform electric field. Dual sensors are an integral part of a new method for measuring inhomogeneous electric fields by average value. Experimental studies are aimed at confirming the possibility of using dual sensors in inhomogeneous electric fields and the method of measuring the electric field strength by the average value. To carry out experiments in a non-uniform electric field, a high-voltage measuring setup is created. The measuring setup made it possible to obtain the static characteristics of a dual sensor in an inhomogeneous electric field. Comparison of the static characteristics obtained in a homogeneous and inhomogeneous field makes it possible to estimate their errors and compare these errors with theoretically calculated ones. The comparison results have showed that the discrepancy between the static characteristics does not exceed +1,5 %, and the discrepancy in the errors of the dual sensor, estimated from experimental data in an inhomogeneous field and obtained theoretically, does not exceed ±2 % in absolute units. The obtained research results allow us to confirm the adequacy of the theory underlying the theoretical provisions laid down in the calculations of dual electric induction spherical strength sensors of the electric field.